How internet memes develop vocabulary proficiency among EFL university students - Suryawijaya, Danar; Priyatmojo, Arif Suryo (ELT Forum: Journal of English Language Teaching, 2025)
This article explores how internet memes aid university students learning English as a Foreign Language (EFL) in getting better at vocabulary acquisition. It argues that because of the nature of internet memes, memes use words and pictures, are often funny, and are part of popular culture, they are a new and unique way to learn and remember words used in daily communication. The article explains a simple plan showing how using memes can help students understand words better, remember them, and use them more actively and effectively. It shows how important it is to use resources from the digital world to make learning English more interesting, engaging, and useful. And the discussion ended with the suggestion that to improve language skills, we don't need to stick to traditional techniques; we can also get media and learning methods online, or even use both. One of the ways to improve language skills is by using internet memes because memes are equipped with several characteristics that make learning fun. However, it is important to note that we cannot rely on internet memes alone; it is better to use internet memes as supplementary tools.